Reliability and discriminative validity of sudden ankle inversion measurements in patients with chronic ankle instability - Eechaute, Christophe; Vaes, Peter; Duquet, William; Van Gheluwe, Bart (Gait & posture, 2009)
Studies investigating peroneal muscle reaction times in chronically unstable ankle joints present conflicting results. The degree of reliability and accuracy of these measurements is unknown in patients with chronic ankle instability (CAI). 40 patients with CAI and 30 healthy subjects were tested using a sudden ankle inversion of 50° while standing on a trapdoor device. Sudden ankle inversion measurements were registered using electromyography, accelerometry and electrogoniometry. For reliability testing, intra-class coefficients (ICCs; model 3,1) and standard errors of measurements of the latency time, motor response time and electromechanical delay of the peroneus longus muscle, the time and angular position of onset of decelerations, the mean and maximum inversion speed and the total inversion time were calculated in 15 patients with CAI. To assess between-group differences, t-tests for independent samples (p<.05) were used. ICCs ranged from .20 (angular position of onset of the second deceleration) to .98 (electromechanical delay of the peroneus longus muscle). Significant between-group differences were observed in only 2 of the 12 variables (for the electromechanical delay of the peroneus longus muscle, p=.001; time of onset of the second deceleration, p=.040). The latency time and motor response time of the peroneus longus muscle, the total inversion time and the mean inversion speed demonstrate acceptable reliability in healthy subjects and patients. The latency time and motor response time of the peroneus longus muscle are not delayed in patients with CAI. Ankle inversion measurements are not discriminative for CAI.